2017
DOI: 10.1038/s41598-017-16156-0
|View full text |Cite
|
Sign up to set email alerts
|

Remapping high-capacity, pre-attentive, fragile sensory memory

Abstract: Humans typically make several saccades per second. This provides a challenge for the visual system as locations are largely coded in retinotopic (eye-centered) coordinates. Spatial remapping, the updating of retinotopic location coordinates of items in visuospatial memory, is typically assumed to be limited to robust, capacity-limited and attention-demanding working memory (WM). Are pre-attentive, maskable, sensory memory representations (e.g. fragile memory, FM) also remapped? We directly compared trans-sacca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
4
18
1
1
Order By: Relevance
“…3 that can be due to a stronger prediction of the upcoming stimulus and therefore a stronger phantom percept. Our results are in agreement with recent studies demonstrating the existence of a partial but systematic transsaccadic integration of visual features across saccades 15 17 , 19 , 26 , 42 as well as the neural signature of the transsaccadic memory 43 , 44 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3 that can be due to a stronger prediction of the upcoming stimulus and therefore a stronger phantom percept. Our results are in agreement with recent studies demonstrating the existence of a partial but systematic transsaccadic integration of visual features across saccades 15 17 , 19 , 26 , 42 as well as the neural signature of the transsaccadic memory 43 , 44 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it was proposed that the detailed presaccadic information, the stimulus features and its precise position are not transferred, nor integrated across saccades 11 14 . Recent studies however changed this view, showing that low level, pre- and postsaccadic image visual features such as orientation 15 17 color 18 20 or spatial frequency 21 are indeed partially transferred and integrated across the saccade, probably through remapping mechanisms 22 26 . Importantly for the context of the present study, it was also shown that relatively precise information of object location can be maintained across saccades and be almost perfectly recovered if the attended object is briefly blanked at the onset of the saccade 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was further supported by several subsequent studies (Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Puntiroli, Kerzel, & Born, 2015). However, in recent years a number of studies have provided evidence that feature information, in addition to attentional pointers, is also involved in transsaccadic remapping (Cha & Chong, 2013;Demeyer, De Graef, Wagemans, & Verfaillie, 2009, 2010Demeyer, Graef, Verfaillie, & Wagemans, 2011;Eccelpoel, Germeys, Graef, & Verfaillie, 2008;Edwards, VanRullen, & Cavanagh, 2017;Fracasso, Caramazza, & Melcher, 2010;Gordon, Vollmer, & Frankl, 2008;Habtegiorgis, Rifai, Lappe, & Wahl, 2018;Harrison & Bex, 2014;Hayhoe, Lachter, & Feldman, 1991;He et al, 2017;Herwig & Schneider, 2014;Koller & Rafal, 2018;Melcher, 2007;Nakashima & Sugita, 2017;Oostwoud Wijdenes, Marshall, & Bays, 2015;Paeye, Collins, & Cavanagh, 2017;Prime, Niemeier, & Crawford, 2006;Prime, Vesia, & Crawford, 2011;Sligte et al, 2017;Wittenberg, Bremmer, & Wachtler, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013;Zimmermann et al, 2017;Zimmermann, Weidner, Abdollahi, & Fink, 2016;Zirnsak et al, 2011). Our study is in line with these studies, and further...…”
Section: Remapping Of Features or Attentional Pointers?supporting
confidence: 92%
“…saccades. Although saccades dramatically alter the visual input, we subjectively experience a stable visual world, that is, a world in which items of interest are available for processing both before and after a saccade [24,25]. Therefore, with each new fixation, our brain has to integrate the old and new retinal images with information about the current eye position and the magnitude and direction in which gaze was displaced by the most recent saccade.…”
Section: Discussionmentioning
confidence: 99%